Contextual-Based Drill Method in Developing Beginning Reading Skills of Children with Learning Difficulties: Metode Latihan Berbasis Kontekstual dalam Mengembangkan Kemampuan Membaca Permulaan Anak dengan Kesulitan Belajar - Masirri, Natalia; Purwanta, Edi (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Early reading skills are crucial for children’s literacy development, especially for those experiencing learning difficulties. Specific background: Traditional methods are often less responsive to the individual needs of students with learning challenges, leading to poor comprehension and motivation. Knowledge gap: Few studies have systematically examined how contextual-based drill methods can be adapted for learners with reading difficulties. Aims: This study investigates how a contextual-based drill method supports the development of beginning reading skills among second-grade elementary school students with learning difficulties. Results: Using a quasi-experimental pretest-posttest design with six students, the Wilcoxon Signed Rank Test (p < 0.05) indicated a significant improvement in letter recognition, word formation, and comprehension after intervention. Novelty: The integration of repetitive drills within meaningful contextual experiences provided a more adaptive and engaging learning structure. Implications: The method can guide teachers in designing inclusive reading instruction that bridges cognitive skill-building and real-life application for early learners. Highlights Students showed significant improvement in letter and word recognition after contextual-based drill sessions. The learning process became more meaningful and engaging through real-life contextual connections. This approach supports inclusive education by adapting repetitive learning to individual student needs. Keywords Contextual-Based Drill, Beginning Reading, Learning Difficulties, Elementary Education, Inclusive Teaching